Exploration of Energy Storage Materials for Water Desalination via Next-Generation Capacitive Deionization - Shi, Wenhui; Gao, Xinlong; Mao, Jing; Qian, Xin; Liu, Wenxian; Wu, Fangfang; Li, Haibo; Zeng, Zhiyuan; Shen, Jiangnan; Cao, Xiehong (Frontiers in Chemistry, 2020)
Clean energy and environmental protection are critical to the sustainable development of human society. The numerous emerged electrode materials for energy storage devices offer opportunities for the development of capacitive deionization (CDI), which is considered as a promising water treatment technology with advantages of low cost, high energy efficiency and wide application. Conventional CDI based on porous carbon electrode has low salt removal capacity which limits its application in high salinity brine. Recently, the Faradaic electrode materials inspired by the researches of sodium-batteries appear to be attractive candidates for next-generation CDI which capture ions by the intercalation or redox reactions in the bulk of electrode. In this mini review, we summarizes the recent advances in the development of various faradaic materials as CDI electrodes with the discussion of possible strategies to address the problems present.